Bagaimanakah kebahagiaan perempuan?: Studi fenomenologi deskriptif pengalaman perempuan yang menjalani long distance marriage - Andy Refinia Salsabilla Arifin; Amanda Pasca Rini; Nindia Pratitis (INNER: Journal of Psychological Research, 2023)
Abstract Long Distance Marriage or long-distance marriage relationship is a form of romantic relationship but separated by distance, these two individuals persist even though they have limitations to make physical contact. This research focuses on how happiness is portrayed by women undergoing long-distance marriages in Dusun Tamban. This study used purposive sampling with three subjects whose criteria had been determined. This study uses a qualitative method with the type of descriptive phenomenological research (PFD). Data collection techniques are carried out by observation, and interviews. The data analysis technique used was descriptive phenomenological analysis (DPA). Based on the results of the analysis by carrying out the six stages that the researchers carried out, the results of three participants found three core themes of the participants’ experiences regarding patience, hope, and sadness when away from their husbands. Women who are undergoing long-distance marriages in Dusun Tamban are not completely happy because each participant still has the sadness caused by long-distance marriage. Keywords: Long Distance Marriage, Happiness, Women Abstrak Long Distance Marriage atau hubungan pernikahan jarak jauh ini merupakan bentuk hubungan yang romantis tetapi terpisahkan oleh jarak, dua individu ini tetap bertahan meskipun memiliki keterbatasan untuk melakukan kontak fisik. Penelitian ini berfokus pada bagaimana gambaran kebahagiaan pada perempuan yang menjalani long distance marriage di Dusun Tamban. Penelitian ini menggunakan purposive sampling dengan tiga subjek yang telah ditentukan kriterianya. Penelitian ini menggunakan metode kualitatif dengan jenis penelititan fenomenologis deskripstif (PFD). Teknik pengumpulan data dilakukan dengan observasi, wawancara. Teknik analisis data yang digunakan yakni descriptive phenomenological analysis (DPA), berdasarkan hasil analisis dengan melakukan enam tahapan yang sudah peneliti lakukan diperoleh hasil tiga partisipan yang didapati tiga inti tema pengalaman partisipan mengenai kesabaran, harapan, kesedihan saat jauh dari suami. Perempuan yang menjalani long distance marriage di Dusun Tamban belum sepenuhnya bahagia dikarenakan pada masing-masing partisipan masih memiliki kesedihan yang disebabkan oleh long distance marriage. Kata kunci: Long Distance Marriage, Kebahagiaan, Perempuan